Research reviews and prospects of gut microbiota in liver cirrhosis: a bibliometric analysis (2001–2023) - Zhu, Xiaofei; Zhou, Ziyuan; Pan, Xiaxia (Frontiers in Microbiology, 2024)
Introduction The gut-liver axis has emerged as a focal point in chronic liver disorders, prompting more research into the role of the gut microbiota in liver cirrhosis. In individuals with liver cirrhosis, changes in the structure and function of the gut microbiota are closely tied to clinical prognosis. However, there is a scarcity of bibliometric evaluations conducted in this particular field. Methods This study is aiming to conduct a complete analysis of the knowledge structure and centers pertaining to gut microbiota in liver cirrhosis using bibliometric methods. Publications on gut microbiota and liver cirrhosis from 2001 to 2023 are sourced from the Web of Science Core Collection. For the bibliometric analysis, we employ VOSviewer, CiteSpace, and the R package “bibliometrix”. Results Our study encompasses a comprehensive collection of 3109 articles originating from 96 countries, with notable contributions from leading nations such as the United States and China. The quantity of publications concerning the gut microbiota of liver cirrhosis rises annually. The University of California San Diego, Virginia Commonwealth University, Zhejiang University are the primary research institutions. World Journal of Gastroenterology publishes the most papers in this field, while hepatology is the most frequently co-cited journal. These publications come from a total of 15,965 authors, and the most prolific authors are Bajaj Jasmohan S., Schnabl Bernd and Gillevet Patrick M., while the most co-cited authors are Bajaj Jasmohan S., Younossi Zobair M., and Reiner Wiest. In addition, “dysbiosis”, “gut microbiota”, “intestinal barrier”, “fecal microbiota transplantation”, and “complement-system” are the primary keywords of research trends in recent years. Discussion This study offering a comprehensive insight into the research dynamics surrounding gut microbiota in patients with liver cirrhosis. It delineates the current research frontiers and hotspots, serving as a valuable guide for scholars.